Fenomena Broker Politik dalam Penyelenggara Pemilu - Anindita Pratitaswari; Sri Budi Eko Wardani (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2020)
One of the norms for elections with integrity requires that election administrators behave neutral and impartial. However, since the election period in the reformation era, the integrity issue of the election administrators is still crucial. In practice, there are still cases of electoral fraud involving election administrators. Based on pre-existing cases, the election organizer has become the main actor (broker) in moving several other election administrators to commit crimes that destroy the integrity of the Election by taking sides and accepting bribes from one of the candidates. By using qualitative research methods, this study will understand and analyze a particular social reality of electoral officer events as a political intermediary. As well as conducting a documentary study containing the decision document for violating the code of ethics of the election organizers as well as the 2019 legislative election criminal decision document. The results of this study show that the role of the election organizer broker is different from previous research, namely, the task of connecting candidates with other election administrators to help the candidate's electoral interests by means of a cheat. Meanwhile, if based on previous election criminal cases, the use of election administrators is usually used to manipulate election results.